1997
DOI: 10.1007/bf00881816
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive grading of primary brain tumours: Results of a comparative study between SPET with123I-?-methyl tyrosine and PET with18F-deoxyglucose

Abstract: Use of iodine-123-alpha-methyl tyrosine (123I-IMT) allows investigation of the amino acid transport rate in gliomas. It was the aim of this study to compare the value of measurement of glucose metabolism with that of measurement of 123I-IMT uptake for the non-invasive grading of brain tumours. The study population comprised 23 patients with histopathologically proven primary brain tumours; 14 had high-grade gliomas, and nine low-grade brain neoplasms. Glucose metabolism was studied using an ECAT EXACT 47 posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…As in other studies of gliomas in general, or astrocytomas in particular (25,58,59), features of elevated metabolism were more likely to be seen in high-grade gliomas with an oligodendroglial component, with 201 Tl uptake being more strongly correlated with histopathological grade than 18 F-FDG uptake. Thus, uptake of 201 Tl, being lower in normal brain than uptakes of 18 F-FDG, and requiring blood-brain barrier breakdown, provides a clearer indication of histopathological grade.…”
Section: Discussionsupporting
confidence: 49%
“…As in other studies of gliomas in general, or astrocytomas in particular (25,58,59), features of elevated metabolism were more likely to be seen in high-grade gliomas with an oligodendroglial component, with 201 Tl uptake being more strongly correlated with histopathological grade than 18 F-FDG uptake. Thus, uptake of 201 Tl, being lower in normal brain than uptakes of 18 F-FDG, and requiring blood-brain barrier breakdown, provides a clearer indication of histopathological grade.…”
Section: Discussionsupporting
confidence: 49%
“…Both positive and inverse correlations can be found between metabolic responses and survival, making these data inconclusive so far. In a more recent study, methionine is found to be superior to FDG in monitoring the treatment effects in low-grade astrocytomas [97].…”
Section: Evaluation Of Therapy By Positron Emission Tomographymentioning
confidence: 98%
“…A significant correlation between tumor uptake of MET and survival has also been found in low-grade gliomas [115]. A higher IMT uptake in high-grade gliomas than in low-grade gliomas was described [67,146]. However, IMT-SPECT does not significantly add to the accuracy of MRI in determining the tumor grade [117].…”
Section: Brain Tumors Gliomas Amino Acid Pet and Spect In The Diagnosmentioning
confidence: 87%